On the optimal alpha-k curve of the sample myriad - Lim, Heng Siong; Chuah, Teong Chee; Chuah, Hean Teik (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2007)
The alpha-k (alpha - k) curve is an important tool for real-time myriad filtering problems in channels with time-varying impulsiveness. In this letter, we use the asymptotic variance as the criterion to derive the optimal alpha - k curve. We then suggest a new expression for the optimal curve and compare it to the conjectured expression in earlier works.